Psychological Impact of COVID-19 on Primary Education Teachers in the Basque Country - Arruti, Arantza; Korres, Oihane; Paños-Castro, Jessica (Frontiers in Education, 2022)
COVID-19 has greatly challenged many areas, including those affecting educational systems. Teachers have had to cope with tremendous pressure, stress, and anxiety. The objective of this study is to analyze how primary education teachers in the Autonomous Region of the Basque Country (Spain) perceive the impact that moods and the ensuing consequences of COVID-19 have on their personal and professional spheres. This study used a quantitative methodology based on a dedicated questionnaire. A total of 849 teachers answered the questionnaire and reported that they had felt nervous (x¯: 8.77) and tense (x¯: 8.57), and that they had been shocked by the excessive length of the lockdown (x¯: 7.70) and the restrictions in sports and leisure activities (x¯: 7.59). Significant differences were found according to gender, type of school, socioeconomic environment, age, and years of experience. The study highlights the need to educate both teachers and students so that they can manage and regulate their emotions in unexpected situations. An additional need was identified to enhance teachers’ digital skills to better enable them to face the challenges of the Information and Knowledge Society.